Parents' experiences of infant and young child feeding during the COVID-19 pandemic in Ireland - Elizabeth J O'Sullivan; Aileen Kennedy (Cambridge University Press, 2023)
Abstract Objective: The WHO has urged member states to develop preparedness plans for infant and young child feeding (IYCF) during emergencies. Ireland has no such plan. We aimed to identify the needs of caregivers in Ireland with regards IYCF during the COVID-19 pandemic. Design: Online survey conducted in May-June 2020. Setting: Ireland, during the first period of severely restricted movement due to COVID-19 (lockdown). Participants: Respondents (n 745) were primary caregivers of a child under 2 years; they were primarily well educated and likely of higher socio-economic status. Results: Among those who breastfed, being unable to access breast-feeding support groups and being unable to access in-person, one-to-one breast-feeding assistance were the biggest challenges reported. Nearly three quarters of those who had their babies during lockdown reported these challenges: 72·8 % and 68·8 %, respectively. For those using formula, the main challenges were structural in nature; approximately two-thirds of those who had their baby prior to lockdown feared there would be formula shortages and a third were unable to purchase formula due to shortages. Conclusions: Regardless of how their babies were fed, parents in Ireland experienced multiple challenges with infant feeding during the COVID-19 crisis. Breast-feeding should be protected, supported and promoted, particularly during an infectious disease pandemic. Additionally, assurances around supply of infant formula could reduce parental stress during a pandemic or emergency. An IYCF in emergencies plan would clearly set out how we could best support and protect the nutrition of the most vulnerable members of our population.